CHALLENGES TO TOYOTA CAUSED BY RECALL PROBLEMS, SOCIAL NETWORKS AND DIGITISATION - Jay Rajasekera (Asian Academy of Management Journal, 2013)
The recent recall problems that shook Toyota had raised questions about its openness with the public. The media attention and the intervention by governments in Toyota’s biggest markets in North America, Europe, China, and Japan, had kept the management on the spotlight. The crisis also exposed the power of social media. Though, authoritarian regimes can control social media, public companies cannot do it. They basically have to live with it – either countering effectively, when a crisis starts brewing or suffering the consequences when it grows out of proportions. Had Toyota handled the social media strategically and could it protect the reputation built over the decades as the top quality auto maker in the world by overcoming the recall debacle? And, what challenges the increasingly digitalized auto industry pose for Toyota are the main subjects of this paper.